Phantom - Smith, L. J. (Lisa J.) (Smith, L. J. (Lisa J.). Vampire diaries, the hunters, 2011)
After Elena Gilbert and vampire brothers Stefan and Damon Salvatore help save their town from a demonic spirit, a new evil arrives and sets its sights on Elena, but this time she will only have one brother to protect her.